Apparent Molal Volumes of Aqueous AmmoniumSalts-Glucose Solution - Singh, Hanuman; Singh, K.P.; Bhonsla, A.K.S.; Upadhyay, G.S. (Asian Journal of Chemistry, 2010)
Present paper reports the mean apparent molal volumes of aqueous NH4X (X = Cl, Br, NO3)-glucose solution directly determined at 40ºC from density measurements. The modified Young's rule has been found to be applicable to these solutions. The deviations from the modified Young's rule have been taken as the excess apparent molal volumes of mixing NH4X and glucose solutions.